Si/Si0.7Ge0.3 A2RAM nanowires fabrication and characterization for 1T-DRAM applications. (July 2022) - Lacord, J.; Tcheme Wakam, F.; Chalupa, Z.; Hartmann, J.-M.; Besson, P.; Loup, V.; Vizioz, C.; Brevard, L.; Aussenac, F.; Mescot, X.; Lee, K.; Bawedin, M.
Highlights: A2RAM devices are fabricated using an adaptation of Si-Nanowire process flow. They include a Si-SiGe heterostructure to improve memory performance. Even the device structure is not exactly what we expect, we succeed to evidence 1T-DRAM programming. Abstract: A2RAM devices are fabricated using an adaptation of Si-nanowire process flow, including a Si-SiGe heterostructure. We present the effects of gate length, film thickness, bridge implantation conditions and the presence of LDD impacts on A2RAM memory performance. Despite the accidentally undoped polysilicon gate, we succeed in demonstrating 1T-DRAM programming and operation.